A Multilayer Functionalized Drug-Eluting Balloon for Treatment of Coronary Artery Disease - Hak-Il Lee; Won-Kyu Rhim; Eun-Young Kang; Bogyu Choi; Jun-Hyeok Kim; Dong-Keun Han (MDPI AG, 2021)
Drug-eluting balloons (DEBs) have been mostly exploited as an interventional remedy for treating atherosclerosis instead of cardiovascular stents. However, the therapeutic efficacy of DEB is limited due to their low drug delivery capability to the disease site. The aim of our study was to load drugs onto a balloon catheter with preventing drug loss during transition time and maximizing drug transfer from the surface of DEBs to the cardiovascular wall. For this, a multilayer-coated balloon catheter, composed of PVP/Drug-loaded liposome/PVP, was suggested. The hydrophilic property of 1st layer, PVP, helps to separate drug layer in hydrophilic blood vessel, and the 2nd layer with Everolimus (EVL)-loaded liposome facilitates drug encapsulation and sustained release to the targeted lesions during inflation time. Additionally, a 3rd layer with PVP can protect the inner layer during transition time for preventing drug loss. The deionized water containing 20% ethanol was utilized to hydrate EVL-loaded liposome for efficient coating processes. The coating materials showed negligible toxicity in the cells and did not induce pro-inflammatory cytokine in human coronary artery smooth muscle cells (HCASMCs), even in case of inflammation induction through LPS. The results of hemocompatibility for coating materials exhibited that protein adsorption and platelet adhesion somewhat decreased with multilayer-coated materials as compared to bare Nylon tubes. The ex vivo experiments to confirm the feasibility of further applications of multilayer-coated strategy as a DEB system demonstrated efficient drug transfer of approximately 65% in the presence of the 1st layer, to the tissue in 60 s after treatment. Taken together, a functional DEB platform with such a multilayer coating approach would be widely utilized for percutaneous coronary intervention (PCI).